Suharto's population policy in contemporary Indonesia : family planning program, marriage act or compulsory education has the greatest impact to fertility decline? - Widyastari, Dyah Anantalia; Isarabhakdi, Pimonpan (Public Health of Indonesia, 2016)
Fertility in Indonesia has been falling significantly, from an average total fertility rate of 5.6 children per women in 1970s to 4.1 in 1980, and 2.6 in 2010. This paper attempts to explore which and how Suharto's population policies have played role in Indonesia's fertility decline. Whilst the adoption of modern contraceptive was perceived as the major determinant of fertility decline in Indonesia, changes in Indonesia's political order and socio-economic development also contribute a considerable effect to Indonesians' familial norms. The implementation of  9-year compulsory education had placed a strong foundation for the future Indonesian human capital and enabled women to obtain higher opportunities for schooling. Beside facilitates the diffusion of ideas among young people and opened up their perspective toward reproductive rights and self actualization, education also increases women's opportunities to participate in laborforce. With the increasing roles outside the domestic sector, delaying age of marriage and limiting family size becomes a choice for women in contemporary Indonesia. The marriage act, however, was perceived as an accelerator rather than a predictor in increasing age of first marriage. Regardless the existence of the Marriage Law 1974, age of first marriage is likely to increase with increasing of education, although maybe in a slower rate.